Effects of green solvents and surfactants on the characteristics of few-layer graphene produced by dual-frequency ultrasonic liquid phase exfoliation technique - Tyurnina, Anastasia V.; Morton, Justin A.; Kaur, Amanpreet; Mi, Jiawei; Grobert, Nicole; Porfyrakis, Kyriakos; Tzanakis, Iakovos; Eskin, Dmitry G. (Carbon)
Nowadays, one of the promising methods for scalable graphene production is ultrasound-aided liquid phase exfoliation (ULPE) of graphite. Two current limiting factors of ULPE are the use of harmful solutions (such as NMethyl-2-pyrrolidone or Dimethylformamide) and a relatively low graphene yield. In this study, we demonstrate a new dual frequency (20 kHz and 1174 kHz) ULPE approach in various eco-friendly media, which enabled us to produce various few-layer graphene (FLG) solutions of high quality. By implementing sophisticated characterisation techniques consisting of Raman spectroscopy, UV–vis spectroscopy and high-resolution electron microscopy, the final graphene flakes structure was confirmed to correlate the properties of each individual solution. The thinner (~3 layers) and larger (~1.5 μm2) flakes were observed while using just water, with the highest yield (11%) of smaller FLG flakes to be achieved in the mixture of water and a surfactant. In order to understand the cavitation mechanism in different solutions, the ULPE process was investigated by acoustic measurements. This study demonstrates the crucial role of ethanol (as a solvent) and surfactants as it regulates the cavitation power and intensity of the ultrasonic field and, thereby, the cavitation effectiveness. It is suggested that the mixture of water, ethanol and a surfactant is the best medium for ULPE process where a high yield of low-defective FLG flakes can be obtained in a solution stable at least for 3 months (around 80%)